Analisis Sudut Kemiringan Optimum Panel Surya Atap di Kota Jakarta Menggunakan Data Global Solar Atlas - andi Makkulau; Nurmiati Pasra; Samsurizal Samsurizal; Bayu Lanzardi Yahya; M Abyan Alwan (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2026)
The utilization of rooftop solar photovoltaic (PV) systems in urban areas has gained significant momentum as part of the energy transition strategy. Determining the optimum tilt angle of PV panels is crucial in maximizing system output. This study aims to analyze the optimum tilt angle for rooftop PV with multiple linear regression in five administrative cities of Jakarta using solar resource data from the Global Solar Atlas. Annual energy yield data were evaluated at an azimuth of 0° (facing north) with tilt angle variations from 0° to 20° in 1° intervals. The analysis employed a quadratic regression model estimated using Ordinary Least Squares (OLS), with uncertainty assessment conducted through 1000 bootstrap iterations. Results indicate that the optimum tilt angle ranges between 5° and 9°, with intercity variations: West Jakarta (5°), North Jakarta (9°), Central Jakarta (7.5°), East Jakarta (8.2°), and South Jakarta (7°). Energy gains compared to the horizontal orientation (0°) are relatively small, less than 1.1%. These findings suggest that for practical rooftop installations in Jakarta, a tilt angle of 7–9° can be recommended, as performance differences with continuous optimum estimation are negligible.Keywords - Global Solar Atlas, Jakarta, Optimum Tilt Angle, Quadratic Regression, Rooftop Solar PV